ANALYSIS OF LITHIUM-ION NICKEL-COBALT-ALUMINA (NCA) BATTERY CELL SUBJECTED TO AXIAL, BENDING, AND LATERAL LOADING CASES - FADILLAH (NIM: 13614059), HAFIZ
In recent years, battery usage is not limited to power small electronic devices, but It has extended its usage as the power source of battery-based electric vehicle. Understanding of the battery cell failure characteristic is paramount due to the high risk of thermal runaway that could initiated from a damaged cell. This thesis will focus on the study of the force-displacement response of Nickel-Cobalt-Alumina (NCA) variant of Lithium-ion battery cell on axial, bending, and lateral loading cases on quasi-static and dynamic loading scheme. For the dynamic loading scheme, the loading velocity will be varied at 5 m/s, 10m/s, 15 m/s, and 30 m/s to observe the strain-rate effect to the force-displacement response of the battery cell. The research will be performed by simulating the loading cases numerically using an already existing model. The results of the quasi-static loading scheme will be compared to the reference and the model shall be used for the dynamic loading scheme. The dynamic loading scheme simulation shows that, generally, the increase of the loading velocity will correspond to the increase of the peak force that can be handled by the battery cell compared to the quasi-static loading scheme. The displacement where peak force occurs also extend further from the quasi-static result.